Investigating the Role of Gamification in Motivating Students Learning - Si, Josh Chong En; Karuppiah, Nanthakumar; Mahindran, Nirmal Kumaar; Law, Kyra Ley Sy (Society of Visual Informatics, 2025)
This study investigates the role of gamification in enhancing student motivation within higher education, specifically targeting bachelor’s degree students in Klang Valley, Malaysia. The objective is to examine how the ARCS-R model by integrating the ARCS motivational framework (Attention, Relevance, Confidence, Satisfaction) with the Relatedness component of Self-Determination Theory (SDT) influences student motivation. A quantitative approach was employed, involving 208 business students who engaged in gamified learning activities via the Socrative platform. Participants completed competitive and collaborative tasks, followed by a survey measuring motivational constructs. Partial Least Squares Structural Equation Modelling (PLS-SEM) was utilized for data analysis. The results indicated that Relevance, Confidence, Satisfaction, and Relatedness had significant positive effects on student motivation, while Attention did not show a significant impact. The findings suggest that although gamified environments can enhance motivation, some elements, such as Attention, may be less effective without dynamic game design features. The study underscores the importance of integrating more interactive and adaptive game mechanics to sustain learner engagement. This research contributes to the understanding of motivation theories in gamified learning, offering empirical support for combining ARCS and SDT models. Future research should explore longitudinal effects and the role of personalized gamification strategies to optimize motivational outcomes across diverse student populations.